A variety of Gronwall Inequalities of Fractional Variable Order - Anastassiou, George A. (Journal of Applied Nonlinear Dynamics, 2026)
A wide variety of Gronwall inequalities of fractional variable order is presented. These are of left and right sides, applications follow. This new research strongly supports the new trend of Fractional Calculus of variable order, see [1].